Estudo da interação não-nativa no enovelamento de proteínas - Mouro, Paulo Ricardo [UNESP] (2014)
The study of physicochemical principles which governs the folding process became central in order to provide answers for the protein folding mechanism. In this context, the energy landscape theory has been supporting theoretical and experimental advances in the understanding this mechanism. The energy landscape of globular proteins resembles a funnel of structures progressively folded en route to the native state, minimally frustrated state. It is well established that an addition of small amount of energetic frustration enhances folding speed for certain proteins. We applied the Cα structure-based model to simulate a group of proteins with the contact order (CO) as the reaction coordinate and we found that CO and free energy barrier at the transition state ( F) correlates with nonnative contacts variation ( A) at the optimum frustration regime. We also found that F and A cluster the simulated proteins by their fold motifs. These computational findings are corroborated by analytical model. As a consequence, optimum frustration regime for protein folding can be predicted analytically